Prevalence thresholds for wasting, overweight and stunting in children under 5 years. Issue 1 (9th October 2018) - de Onis, Mercedes; Borghi, Elaine; Arimond, Mary; Webb, Patrick; Croft, Trevor; Saha, Kuntal; De-Regil, Luz Maria; Thuita, Faith; Heidkamp, Rebecca; Krasevec, Julia; Hayashi, Chika; Flores-Ayala, Rafael
Abstract: Objective: Prevalence ranges to classify levels of wasting and stunting have been used since the 1990s for global monitoring of malnutrition. Recent developments prompted a re-examination of existing ranges and development of new ones for childhood overweight. The present paper reports from the WHO–UNICEF Technical Expert Advisory Group on Nutrition Monitoring. Design: Thresholds were developed in relation tosd of the normative WHO Child Growth Standards. The international definition of 'normal' (2sd below/above the WHO standards median) defines the first threshold, which includes 2·3 % of the area under the normalized distribution. Multipliers of this 'very low' level (rounded to 2·5 %) set the basis to establish subsequent thresholds. Country groupings using the thresholds were produced using the most recent set of national surveys. Setting: One hundred and thirty-four countries. Subjects: Children under 5 years. Results: For wasting and overweight, thresholds are: 'very low' (<2·5 %), 'low' (≈1–2 times 2·5 %), 'medium' (≈2–4 times 2·5 %), 'high' (≈4–6 times 2·5 %) and 'very high' (>≈6 times 2·5 %). For stunting, thresholds are: 'very low' (<2·5 %), 'low' (≈1–4 times 2·5 %), 'medium' (≈4–8 times 2·5 %), 'high' (≈8–12 times 2·5 %) and 'very high' (>≈12 times 2·5 %). Conclusions: The proposed thresholds minimize changes and keep coherence across anthropometric indicators. They can be used for descriptive purposes to map countries according to severity levels; by donors and global actors to identify priority countries for action; and by governments to trigger action and target programmes aimed at achieving 'low' or 'very low' levels. Harmonized terminology will help avoid confusion and promote appropriate interventions.